RA92A recombinant protein as immunogen to protect cattle against tick challenge in Brazil and Uganda - Rodrigo Casquero Cunha; Margaret Saimo-Kahwa; Marcos Valério Garcia; Francisco Denis Souza Santos; Emukule Samuel; Nanteza Ann; Kokas Ikwap; Claire Julie Akwongo; Fábio Pereira Leivas Leite; Renato Andreotti (Bioscience Journal, 2021)
In this study, the recombinant gut protein rRa92A produced in Pichia pastoris yeast cells was used to immunize cattle in two experiments, one in Brazil and the other in Uganda. In both experiments, the animals were intramuscularly (IM) injected with 200 µg of recombinant protein in Brazil on days 0, 30 and 51 and in Uganda on days 0, 30. Blood samples for sera separation were collected from different days in both experiments. These samples were analyzed by ELISAs. In Brazil, ticks collected from the animals during the experimental period were analyzed for biological parameters. At Uganda, blood was collected to assess blood parameters, clinical signs were recorded and adult tick (Rhipicephalus appendiculatus) counts were performed. All animals of the vaccinated groups were shown to produce antibodies, and it was not possible to detect an effect on Rhipicephalus microplus. All the clinical parameters were considered within the normal ranges for both the experimental and control groups in Uganda. Antibody absorbance was elevated after each immunization and remained high until the end of the experiments, remaining low in the control animals. The results of stall test carried out in Brazil using R. microplus tick showed efficacy of 21.95%. The rRa92A immunization trial experiments in Uganda showing a decrease of 55.2% in the number of engorged adult ticks, which was statistically significant (p<0.05). Assessment of the immunogenicity of Ra92A produced in the P. pastoris expression system in bovines is reported for the first time, and the protein acted as a concealed antigen.